Flyfishing for coarse fish : Pike, Rudd, Carp, Roach, Perch, Barbel, Chub. Zander, Dace, Tench, Bream, and other fish /: Pike, Rudd, Carp, Roach, Perch, Barbel, Chub. Zander, Dace, Tench, Bream, and other fish. (2015) - Unknown
No abstract available